The evolution of false self-employment in the British construction industry: a neo-Polanyian account of labour market formation - Behling, Felix; Harvey, Mark (Work, Employment & Society, 2015)
Governments in Europe and elsewhere have renewed their attention to the fiscal regulation of their economies in order to close tax loopholes and boost revenues in response to the financial crisis. The article uses a neo-Polanyian ‘instituted economic process’ approach to explore and explain the uniquely high level of bogus self-employment in the UK construction industry, facilitated by confused law and stimulated by a bespoke construction fiscal regime, resulting in endemic tax evasion. It examines how the co-evolution of employment status law and a sector-specific fiscal regime maps tightly onto the emergence of mass self-employment, as evidenced by comparative labour market and sectoral statistics. Seeing competition as an instituted process within these distinctive market arrangements, it identifies a form of ‘degenerative competition’, driving out both genuine direct-employment and self-employment, and driving in bogus self-employment, with its attendant substantial fiscal losses, failed skill reproduction and poor productivity.
Sociology
Keywords: British construction industry; Great Britain; bogus self-employment; business revenue; construction industry; economic sociology; instituted economic process; labour market formation; self-employment; tax evasion; tax loopholes

Sharing Economy: A Step towards the Re-embeddedness of the Economy? - Pais, Ivana; Provasi, Giancarlo (Stato e Mercato, 2015)
The expression "sharing economy" has spread exponentially in the past few years, a sign of the growing interest in a phenomenon that continues to maintain boundaries that are somewhat vague. The hypothesis of this paper is that this can be attributed not only to the pervasiveness and enabling power of new technologies but also to the need to fill a social vacuum due to the failures of the market and the state. The sharing economy is introducing collaborative social forms able (at least ideally) to embed economic relations within social ones. To test this hypothesis, the article uses the instrumentation implemented by Karl Polanyi to analyze the forms of integration of economy and society (exchange, reciprocity, redistribution). The political economy of the late twentieth century was especially interested in exchange (market) and redistribution (state), leaving social reciprocity in the background. However, we have to look at this more carefully to grasp any social and institutional innovation that the sharing economy can promote. The first part of this paper is devoted to an analysis of the forms of integration and, in particular, to reciprocity in its different variants. The second part, in light of the taxonomy proposed in the first, analyzes some of the most significant experiences of the sharing economy, seeking to determine the institutional characteristics and social dynamics that this could (at least potentially) engender and support. The conclusions will attempt to answer the questions formulated and indicate avenues for further research.
Economics; Sociology
Keywords: cooperative enterprises; economic anthropology; economic sociology; market structure; pricing; and design; open source products and markets; other economic systems: general; prices; public goods; reciprocity; renewable resources and conservation: demand and supply; sharing economy; social and economic stratification

Re-Imagining Economic Sociology - Aspers, Patrik; Dodd, Nigel (Oxford University Press, 2015)
The purpose of this book is to explore new developments in the field of economic sociology. It contains cutting-edge theoretical discussions by some of the world's leading economic sociologists, with chapters on topics such as the economic convention, relational sociology, economic identity, economy and law, economic networks and institutions. The book is distinctive in a number of ways. First, it focuses on theoretical contributions, by pulling together and extending what the contributors believe to be the most important theoretical innovations within their own particular areas of the field. Second, there are contributions by leading economic sociologists from both the US and Europe, which gives the book both wider scope and appeal, while also creating the opportunity for some interesting dialogue between distinct theoretical traditions. The book will be of interest to researchers, Ph.D. students, and advanced students on both side of the Atlantic, and indispensible in advanced economic sociology courses.
Sociology
Keywords: business & economics; economic sociology; economic theory; social science / sociology / general

Disembedded markets as a mirror of society - Deutschmann, Christoph (European Journal of Social Theory, 2015)
In the Marxist tradition, capitalism is understood as a commodified society based on markets. The article argues that the ultimate justification of this position does not lie in any ‘materialistic’ approach, but in the disembedding of markets that was the result of the historical ‘Great Transformation’ analysed by Karl Polanyi. Disembedded markets are not an economic subsystem within society but take the place of the most encompassing social system, which Durkheim had reserved for religion. The article distinguishes between spatial, social, material and temporal dimensions of disembedding, thereby elaborating and correcting the analysis of Karl Polanyi. As a genuine form of society, disembedded markets give rise to the epistemological dilemma, which, as Luhmann had shown, is fundamental to any encompassing social theory: Society as a whole cannot be viewed by any observer. According to this viewpoint, economic theories take on ‘theological’ functions, as they provide rationality and legitimacy to a reality that is unknowable.
Sociology
Keywords: Marxist philosophy; capitalism; disembedded markets; disembedding; markets; religion; social theory; uncertainty

Polanyi in the European Single Market: The Re- Regulation of Insurance - Mabbett, Deborah (Economic Sociology: The European Electronic Newsletter, 2015)
This article discusses the difference between a social policy approach to the regulatory embedding of a market and a moral economy approach using the insurance case wherein the European Union's Court of Justice ruled that insurers may not discriminate on grounds of sex in identifying risks.
Political Science; Sociology
Keywords: Court of Justice of the European Union; insurance; lawsuits & claims; reembedding; regulation; social policy

A hidden counter-movement? Precarity, politics, and social protection before and beyond the neoliberal era - Harris, Kevan; Scully, Ben (Theory & Society, 2015)
To grasp what might exist beyond neoliberalism, we need to rethink the history of development before neoliberalism. This article makes two arguments. First, for poorer countries, processes of commodification which are highlighted as evidence of neoliberalism often predate the neoliberal era. Third World development policies tended to make social and economic life more precarious as a corollary to capital accumulation before neoliberalism as an ideology took hold. Second, the intense theoretical and discursive focus on neoliberalism has obscured a tangible shift towards de-commodification in much of the global South. The most salient examples today are state-led social assistance programs that have been implemented across the former Third World. These emerged not out of technocratic fixes from above but often out of political and social struggles from below. The rise and spread of these programs are not only in stark contrast to popular conceptions of a neoliberal reinforcement, but are also specifically targeted at social strata whose precarity commonly originated in developmental policies before the neoliberal era. Utilizing a database of 183 active flagship social assistance programs in 84 developing countries, we present macro-level quantitative evidence of the rise and spread of social protection policies over the past two decades in the global South. We then detail these programs for four middle-income countries-China, Brazil, India, and South Africa. To those who lament that the 2008 crisis has produced no Polanyian double movement, we argue that these state-driven social assistance policies are such a mechanism.
Sociology
Keywords: Global South; abstracts; countermovement; developing countries; double movement; global south; ideology; labor studies; labour studies; middle-income countries; neoliberalism; peasant studies; social policy; social services; welfare studies

Regulatory Transformations: Rethinking Economy-Society Interactions - Lange, Bettina; Haines, Fiona; Thomas, Dania (Bloomsbury Publishing, 2015)
The issue of whether transnational risk can be regulated through a social sphere goes to the heart of what John Ruggie has described as 'embedded liberalism': how capitalist countries have reconciled markets with the social community that markets require to survive and thrive. This collection, located in the wider debates about global capitalism and its regulation, tackles the challenge of finding a way forward for regulation. It rejects the old divisions of state and market, citizens and consumers, social movements and transnational corporations, as well as 'economic' and 'social' regulation. Instead this rich, multidisciplinary collection engages with a critical theme-the idea of harnessing the regulatory capacity of a social sphere by recognising the embeddedness of economic transactions within a social and political landscape. This collection therefore explores how social norms, practices, actors and institutions frame economic transactions, and thereby regulate risks generated by and for business, state and citizens.A key strength of this book is its integration of three distinct areas of scholarship: Karl Polanyi's economic sociology, regulation studies and socio-legal studies of transnational hazards. The collection is distinct in that it links the study of specific transnational risk regulatory regimes back to a social–theoretical discussion about economy–society interactions, informed by Polanyi's work. Each of the chapters addresses the way in which economics, as well as economic and social regulation, can never be understood separately from the social, particularly in the transnational context.Endorsement'This thought-provoking collection asks the most critical question of our time – how to civilise markets through social accountability and political action. The climate and financial crises we face show how crucial this challenge is. Lange, Haines and Thomas have put together a series of fruitful case studies of the possibilities for embedding economic relationships in social relationships by a series of top-class researchers within their own illuminating and sensitive framing of the issue'.Professor Christine Parker, Professor of Regulatory Studies at Monash University.
Law; Sociology
Keywords: administrative law & regulatory practice; economic regulation; economic sociology; embedded liberalism; social regulation; socio-legal studies

Markets, Nature, and Society Embedding Economic & Environmental Sociology - Kaup, Brent Z. (Sociological Theory, 2015)
Social scientists have drawn on theories of embeddedness to explain the different ways legal, political, and cultural frameworks shape markets. Often overlooked, however, is how the materiality of nature also structures markets. In this article, I suggest that neo-Polanyian scholars, and economic sociologists more generally, should better engage in a historical sociology of concept formation to problematize the human exemptionalist paradigm their work upholds and recognize the role of nature in shaping markets and society. Unearthing nature in the work of Karl Polanyi, I develop a theory of embeddedness that more closely accounts for the economic, the social, and the ecological. In doing so, I provide a way for scholars to conceptualize both how market societies shape nature and how nature shapes market societies.
Sociology
Keywords: ecology; embeddedness; environmental sociology; materiality; socionatural

Karl Polanyi and the Problem of Corporate Social Responsibility - Moncrieff, Lilian (Journal of Law and Society, 2015)
This article considers Corporate Social Responsibility (CSR) as part of the projects in ‘new governance and decentred regulation’, which draw social forces towards the regulation of economic behaviour. It uses Karl Polanyi to open up pertinent interfaces between society and economy for observation, and Gunther Teubner to substantiate a ‘regulatory’ view of the company's social relationships. The article finds that CSR combines movements for the recognition of social relationships, on an unprecedented scale, with rigorous simultaneous movements for market building and social abstraction. Twenty-first-century market economy is defined by a capacity to contain ‘the social,’ which is thrown between the two movements, creating opportunities for companies to void the market's social limits. The article counterposes that the social that ‘returns’ after marketization needs to find its way past market-building CSR, to constructively unshackle and redefine the framing of social conflicts that concern the corporation.
Law; Sociology
Keywords: CSR; corporate social responsibility; marketization

Hard cash, easy credit, fictitious capital: Critical reflections on money as a fetishised social relation - Jessop, Bob (Finance and Society, 2015)
Sociology
Keywords: Marxism; commodity; credit; debt; fictitious capital; money

Marketization: Theoretical Reflections Building on the Perspectives of Polanyi and Habermas - Ebner, Alexander (Review of Political Economy, 2015)
The concept of marketization denotes the expansion of market coordination into non-market coordinated social domains as well as its intensification in already market-dominated settings. This article sets out to reconstruct an institutionalist theory of marketization. As a point of departure, it critically examines the related contributions of Karl Polanyi and Jürgen Habermas. The analytical strength of Polanyi's theory of marketization lies in the discussion of the contested embeddedness of markets and the view of marketization as a politically shaped process of institutional change. This concern with the societal expansion of markets is further developed in the Habermasian thesis of the ‘colonisation of the lifeworld’. However, both Polanyi and Habermas lack a specification of the social substance of markets and thus tend to underestimate the complexity of marketization. To address this issue, the present article utilizes the concept of collective goods to introduce new arguments about the institutional dynamics of marketization in the diverse fields of society.
Sociology; Political Science
Keywords: HABERMAS; Jurgen; collective goods; economics; embeddedness; marketization; markets; socioeconomics

Marketization and the public-private divide - Rekhviashvili, Lela (International Journal of Sociology & Social Policy, 2015)
Purpose – The purpose of this paper is to critically examine the reasons behind a decade long contestations between the Georgian government and the petty traders over the access to the public space for commercial use. Design/methodology/approach – The paper relies on the repeated ethnographic fieldwork conducted in Tbilisi in 2012 and 2013. The ethnographic interviews with legally operating traders and illegal street vendors are supplemented by the in-depth interviews with the representatives of the city government and secondary literature on Georgia’s post-revolutionary transformation. Findings – Bridging the critical literature on the politics of the public space with Polanyi’s theory on commodification of fictitious commodities as a precondition of establishment of a market economy, the author argues that for the Georgian government control of the public space was necessary to pursue neoliberal marketisation policies. These policies required removal of the petty traders from public spaces because the state needed to restrict access to public space and limit its commercial usage to delineate public and private property and allow commodification of the urban land and property. As the commodification intensified and the rent prices started growing and fluctuating, the access to the public space became even more valuable for the petty traders. Therefore, the traders developed subversive tactics undermining the division between public and private space and property. Originality/value – The paper demonstrates the importance of enforcing the public-private divide in the process of establishing a market economy in transitional settings. Moreover, it illustrates little discussed social costs of establishing such a divide.
Sociology
Keywords: Tbilisi; commodification; fictitious commodities; informal economy; marketization; municipal government; neoliberalism; petty trade; public space; public spaces; public-private sector cooperation; transition economies

The Neoclassical Origins of Polanyi’s Self-Regulating Market - Gemici, Kurtuluş (Sociological Theory, 2015)
This article shows, through a detailed examination of Karl Polanyi’s published works and unpublished writings, that Polanyi relies heavily on the neoclassical economics of his time in his conceptualization of the market in capitalist societies. This approach is instrumental to the thesis of The Great Transformation concerning the destructive impact of the market on society. However, such an analytical perspective neglects the social character of the market economy. This perspective is also deficient in capturing why the market is destructive to the social fabric. By identifying the origins and limitations of Polanyi’s self-regulating market, this article contributes to critical reevaluations of his work that aim to expand the scope of Polanyian analysis. In particular, this article outlines how the analysis of the market’s contradictory place is not predicated on the notion of self-regulation. Polanyi’s own historical work, as opposed to his theoretical articulations, illustrates such an analysis.
Sociology
Keywords: double movement; neoclassical economics; self-regulating market

Migration, Precarization and the Democratic Deficit in Global Governance - Schierup, Carl-Ulrik; Ålund, Aleksandra; Likić-Brborić, Branka (International Migration, 2015)
This article attempts to provide a critical understanding of the dual signification of “precarity”. It explores what “precarity” as a concept may potentially offer to studies of the changing contemporary political economy of migration. It discusses shifting trends in global migration and point to tendencies for a possible convergence between “South” and “North”, “East” and “West”. Based on a review of current advances in research, it discusses, with reference to the classical work of Karl Polanyi, the potential for a contemporary “countermovement” which would challenge the precarity of migrants. Bringing forward the issue of the “space for civil society” the article addresses a still lingering democratic deficit in the global governance of migration. Policy Implications The article is relevant to policymakers, trade unions and civil society organizations. It contributes to the understanding of policy making processes in emerging multilevel global governance and focuses on issues of precarization, migration, and the implementation and accountability of human, migrant and labour rights.
Sociology; Anthropology
Keywords: countermovement; democratic deficit; ethnicity; global governance; migration; precarity; social welfare studies

Between Marx and Polanyi: New labour mobilisations in the Italian crisis - Caruso, Loris (Capital & Class, 2015)
The current scenario in western countries is characterised by a crisis over the last thirty years of class conflict; by the mainly negative consequences of globalisation and of the transformations by production processes of the mobilising strength of work; by the cancellation of the relationship between labour and political representation; by the difficulties of traditional trade unionism; and by the emergence of the social movement unionism (SMU) paradigm. In this article, these phenomena are analysed from the point of view of the workers’ struggles against the closure of factories. The analysis concerns the mobilisation factors on which the struggle rests; the presence or absence, in the representations of workers, of references to class conflict; the major proximity of these mobilisations to the paradigm of traditional syndicalism or to the SMU paradigm; and the prevalence within them of the Marxist or the Polanyian root of conflict. This analysis is mainly based on an empirical study carried out in an engineering company in the province of Milan, Italy.
Sociology
Keywords: MARX; Karl; 1818-1883; class cleavage; class conflict; crisis; globalisation; globalizaton - research; labor mobility; labor unions; labour mobilisations; labour mobility; labour unions; research; social conflict; social movements

Gellner’s genealogy of the open society: Biopolitics as fragment and remainder - Ryan, Kevin (Thesis Eleven, 2015)
A decade before Foucault began to work with the related concepts of biopolitics and biopower, Gellner posed a series of questions which are suggestive of a similar line of inquiry. Gellner did not pursue this strand of his thought as an historical sociologist however. Instead he packaged it into a functionalist account of how industrial society reproduces itself. In Gellner’s writings, biopolitics is both present and absent, like a redacted text. This is the focus of this article, which locates Gellner’s method of inquiry within a corpus of genealogical studies that includes the work of Polanyi, Weber and Foucault. What distinguishes Gellner is that the history he reconstructs is a story of achievement in the face of terrible historical odds, but this culminates in a normative genealogy that limits the scope for critical analysis. The article concludes by adopting an alternative – yet still Gellnerian – approach to the question of social reproduction, thereby using Gellner to critique Gellner.
Political Science; Sociology
Keywords: FOUCAULT; Michel; 1926-1984; GELLNER; Ernest; biopolitics; biopolitics (philosophy); biopower; genealogy; historical sociology; realism; social aspects

The course, contradictions, and consequences of extending competition as a mode of (meta-)governance: towards a sociology of competition and its limits - Jessop, Bob (Distinktion: Journal of Social Theory, 2015)
This article examines the use of competition as an object and mode of governance. It first considers how competition might become a principle of economic organization and, relatedly, how it may become part of state projects and practices. Second, it comments on the discursive and material dimensions of competition, considering it as a social construct and as a social constraint. Third, it examines the rather idealized representations of competition in the broader doxa of liberalism and neo-liberalism considered in terms of a rough threefold distinction among economic, political, and ideological imaginaries and the limits to the reproduction of these doxa in terms of the complexities of capitalist social relations. Fourth, it explores the complexities of competition in the actually existing world and their role in differential accumulation. In this context it distinguishes neo-classical, Austrian, and Schumpeterian views on competition and entrepreneurship and their contribution to equilibration or creative destruction. Fifth, it considers efforts to steer competition through, inter alia, the competition state and competition law. Sixth, it relates competition to other modes of governance and identifies limits to its role in this regard and introduces ‘meta-governance’ as a response to these limits. Finally, seventh, it comments on the fetishization of competition as a means to subsume society under the dominance of profit-oriented, market-mediated accumulation. It concludes with comments on the limits of competition in relation to fictitious commodities and goods and services that contribute to human flourishing.
Sociology
Keywords: commodification; competition; competition law; competition state; competitiveness; governance; neoliberalism; new public management; social theory

Explaining Political Tunnel Vision: Politics and Economics in Crisis-Ridden Europe, Then and Now - Mudge, Stephanie L. (European Journal of Sociology, 2015)
The grip of austerity in European politics since 2008 presents a double puzzle: electorally weak center-left parties offering no definite alternative, and the surprisingly efficient pursuit of “fiscal consolidation”. To understand this double puzzle this article investigates the institutional bases of alternative economic thinking during the 1930s versus the post-2008 crisis years. Noting the recent prominence of a new social type, the European economist-technocrat (eet), I highlight the historically specific order to which the eet is indigenous: rarefied, international professional circuits that tend to work over, not through, party politics. This contrasts sharply with the nationally-based, party-connected economists who developed new economic orthodoxies between the 1930s and 1960s, including Keynes himself. Approaching the study of economic culture in the public sphere in a Polanyian moral markets framework, I argue that the linkages between European economics and financial technocracies help to explain Europe’s double puzzle. Theoretically, I argue that a focus on expertise and parties, and not just states, is central to our understanding of economic culture in the public sphere. (English)
Sociology
Keywords: European Union; Europäische Union; Frachkenntnisse; Sparmaβnahmen; Union européenne; austerity; austerité; compétence; economics; economists; expertise; partis politiques; political parties; politics and economics; politischen parteien; public sphere; technocracy; wirtschaft; économie

A Neo-Polanyian Theory of Economic Crises - Block, Fred (American Journal of Economics and Sociology, 2015)
This article seeks to use Karl Polanyi's book, The Great Transformation, first published in 1944, to understand the global financial crisis that began in 2008. Polanyi's basic premise was that a great crisis must result from powerful causes. He argued that the crisis of the 1930s was a consequence of three distinct processes: deep imbalances in the global trading system, a crisis within the global financial mechanism that was supposed to manage those imbalances, and a failure of adaptation in the world's leading economy, the United States. The same processes can be seen at work in the last decade.
Sociology
Keywords: global financial crisis

Pursuing a Great Transformation - Evans, Peter (Sociology of Development, 2015)
Polanyi offers a powerful vision of a “great transformation” that will reverse the subordination of society to the economy and reassert the primacy of social protection in the context of modern society. Pursuit of the great transformation is one way of conceptualizing the quest for “development” in the positive sense of ecologically sustainable human flourishing. This paper explores how the contemporary interaction of national and global political dynamics affects the trajectory of Polanyi's “double movement.” Does the shift of economic power to globally organized capital while the space for contentious politics remains primarily at the national level “checkmate” the movement for social protection? Or is there more potential for political contestation and policies supporting social protection at the national level than the “global checkmate” thesis claims? And, if so, can this potential be magnified by productive, synergistic alliances between national and global movements, resulting in a global auxiliary effect instead of a global checkmate effect? Answering these questions requires analyzing the relative autonomy of national political regimes vis-à-vis global capital as well as evaluating the ability of movements to connect effectively across levels.
Sociology
Keywords: Great Transformation; The (Book); double movement; global capital; social protection; transnational social movements

Protecting Markets from Society: Non-Pecuniary Claims in American Corporate Democracy - Gershenson, Carl (Politics & Society, 2015)
The state incentivizes investors to entrust capital to public corporations by granting shareholders enforceable rights over managers. However, these rights create legal “access points” through which social movements can make nonpecuniary claims on the corporation. I use original historical research on the Securities and Exchange Commission’s administration of federal securities law to show that concern over nonpecuniary claims motivates the state to enact the role of “market protector.” In this role, the commission insulates managers of corporations from shareholders’ claims that it deems illegitimate because they are insufficiently profit-oriented. Thus the inverse of Polanyi’s observation that society protects itself from markets is also true: the state creates market boundaries so that “always embedded” markets function more like autonomous, profit-oriented markets. Accordingly, the extent to which corporate democracy represents general, social interests or narrow, profit-oriented interests is largely a function of political contestation and state policy.
Sociology
Keywords: United States; United States Securities & Exchange Commission; corporate accountability; corporate democracy; corporations - government policy; economic sociology; legal status of stockholders; markets; markets - government policy; political sociology; social responsibility of business - United States

Reading The Great Transformation - Martin, Isaac William (Contemporary Sociology, 2015)
Karl Polanyi’s book The Great Transformation is a classic... it has come to be recognized as a founding charter for economic sociology. It anticipated major accomplishments of late-twentieth-century social science (including, among others, Ben Bernanke’s studies of the Great Depression and Amartya Sen’s work on famine). Its core problems—how do societies respond to globalization? how do they address the risks of market failure?—are central to contemporary macrosociology. It is probably time to recognize the canonical status of this book and put it on the classical theory syllabus alongside Marx, Weber, and Durkheim. But The Great Transformation is also—can we admit this about our classics?—a mess. It is conceptually sloppy. Some key terms (such as “market society” and “social dislocation”) are never explicitly defined. Others (such as “a ‘movement’”) are defined with pedantic care, and then used willy-nilly, as if Polanyi forgot what he said the words meant. Important steps in the argument assume what is to be proven. Inconsistencies abound. The treatment of historical sources is casual. To round it all off, the book concludes with a breathtakingly wrong prediction: namely, that the era of market liberalism is over for good—as of 1944. To salvage a theory from all this, let alone one that we can apply to societies in the present day, surely requires a heroic effort of interpretation. Fred Block and Margaret R. Somers undertake the salvage effort...
Sociology
Keywords: BLOCK; Fred L.; Great Transformation; The (Book); Power of Market Fundamentalism: Karl Polanyi's Critique; The (Book); SOMERS; Margaret R.; book review; nonfiction

The Evolution of the Property Relation: Understanding Paradigms, Debates, and Prospects - Davis, Anne E. (Springer, 2015)
Evolution of the Property Relation defines an approach to economics which is centered around the concept of property and explores the historical evolution of the relationship of the individual, private property, and the state, and the distinctive changes wrought by the emergence of the market.
Economics; Sociology
Keywords: business & economics; economic development; economic history; economic theory; labor; labour; management; organizational behavior; social science; sociology; strategic planning

Embedding and disembedding of political elites: a filter system approach - Davis, Aeron (Sociological Review, 2015)
This article looks at the issue of political disengagement in mature democracies and the growing tendency towards disconnect between citizens and their political representatives. It locates itself in relation to 'demand-side' (external to politics) and critical 'supply-side' (focused on the political centre) explanations of disengagement. It concentrates on the latter and, accordingly, builds on critical, post-Marxist and elite-oriented work. As such it follows on from earlier calls in the journal for a return to elite-based research ( Savage and Williams, 2008). Drawing on general concepts in economic sociology ( Polanyi, Granovetter) the article presents an alternative embedding-disembedding paradigm for explaining and evaluating this tendency towards political elite disengagement. The propensity for politicians to disembed from wider society is explained by way of a series of eight 'filters'. Such filters work, alone or cumulatively, both to socially embed political elites within the institutions and networks of formal politics and also to disembed them from wider society and the populace they represent. The interpretive framework outlined here draws on a combination of secondary literature and ongoing interview-based research with some 150 political actors (politicians, journalists, officials) working at Westminster. As such, the filters and embedding-disembedding paradigm focuses primarily on the UK case. However, the framework is easily adaptable to other nations and systems.
Sociology
Keywords: Great Britain - politics & government; communication; disengagement; elite (social sciences); embedding/disembedding; organizations; political communication; political elites; political organizations; political participation laws; politicians

Żeby sprzedać – trzeba dać O rynku i jego nierynkowych fundamentach - Michalski, Michał A. (Prakseologia, 2015)
The paper analyzes interdependence of the market sphere which functions according to the logic of contract, and the sphere of non-market activity within economy, where the logic of gift dominates as a paradigm. The purpose of the analysis is to present how the above concepts of societal exchange intertwine and complete each other within the socio-economic order. This is followed by the description of 'pre-market' economic paradigms (based on Karl Polanyi's contribution) such as reciprocity, redistribution and household. Special attention is paid to category of gift, which is presented as prior to contract and being a necessary condition of the former one. The purpose of the analysis undertaken in this paper is to show how understanding of the interaction discussed here is necessary for creating integrated vision of how socio-economic order functions and offers adequate perspective for formulating recommendations within social and economic policy. (English) "To Sell One Has to Give – of Market and Its Non-Market Foundations"
Sociology; Philosophy
Keywords: contract; economy; gift; gospodarka; kontrakt; market; rynek; socio-economic order; ład społeczno-gospodarczy

Facing an unequal world - Burawoy, Michael (Current Sociology, 2015)
To face an unequal world requires us to interpret and explain it, to be sure, but also to engage it, that is, to recognize that we are part of it and that we are partly responsible for it. In other words, inequality is not just something external to us, but also invades our own world. I begin, therefore, by examining the global community of sociology through the lens of inequality. I then consider two recent perspectives on our unequal world from outside sociology: the moral radicalism of Pope Francis that emphasizes exclusion from market society, and the innovative research of the economist Thomas Piketty that emphasizes unequal inclusion in market society. These two faces of global inequality mirror the social movements reverberating from the economic crisis of 2008 but which have their roots in a reaction to a broader wave of marketization, the third to engulf modern capitalism. To explore the meaning of third-wave marketization, otherwise known as neoliberalism, and the social movements it provokes I draw on two concepts from Karl Polanyi – ‘fictitious commodities’ and ‘countermovement’ – as well as a theory of the dynamics of capitalism. I conclude with three challenges facing a global sociology that centers social movements: to develop a theory that speaks to the globally diverse experiences of commodification; to develop a methodology that recognizes that we are unavoidably participants in the world we study; and to develop a politics that defends a particular vision of that world, a vision that has defined the sociological tradition from its beginning, namely one that upholds the centrality of civil society against the over-extension of market and state.
Sociology
Keywords: globalization; inequality; markets; social movements; sociology

Reforming States, Agricultural Transformation, and Economic Development in Russia and Japan, 1853-1913 - Cohen, Mark (Conference Papers – American Sociological Association, 2015)
Capitalist economic development has occurred unevenly, as certain economies began sustained growth relatively early, opening up an increasingly large gap with lagging countries. This well-known fact has encouraged much research on the prospects for undeveloped economies to "catch up" to the earlier developers. Japan and Russia in the late nineteenth century were two of the first countries outside of western Europe to experience substantial catch-up growth. Beginning in the 1860s, political elites in both countries adopted wide-ranging reforms in pursuit of military modernization and its political and economic prerequisites. This paper analyzes the impact of the two states' reform programs on their countries' rural economies, which represented the vast majority of population and production. Adopting a Polanyian perspective on economic development, this paper finds that only in Japan were agrarian relations transformed so as to set off a process of capitalist economic development centered on rural areas. This divergence is explained by the different stances of the two reforming states towards landlords and peasant communities.
Sociology
Keywords: Japan; Russia; economic development; rural economies

Karl Polanyi's Environmental Sociology - Fenner, Weston Henry, IV; Brechin, Steven R. (Conference Papers – American Sociological Association, 2015)
Drawing upon The Great Transformation (1944), we outline Karl Polanyi's environmental sociology by presenting his major insights on economic substantivism, fictitious commodities, and double movements. Polanyi wrote his opus in challenge to Von Mises' Austrian School of Economics and its pursuit of an autonomous, self-regulating global free market. Polanyi's recognized the social and environmental limits of a fully free market and reasoned that inevitable market excesses would result in the rise of society self-protection to preserve land along with labor and money. We believe Polanyi's insights make him an important classical contributor to environmental sociology on par with Robert Malthus, Karl Marx, Max Weber, and Emile Durkheim. We conclude by outlining possible connections to established environmental sociology theories and literatures.
Sociology
Keywords: double movement; double movements; economic substantivism; environmental sociology; fictitious commodities; market fundamentalism; social theory

Denaturalizing the Market: Primitive Accumulation, Class Reformation, and the Rise of Colombia's Anti-Neoliberal Countermovement - Hough, Phillip A. (Conference Papers – American Sociological Association, 2015)
This paper addresses what labor movement scholars are calling the "Polanyi-problem" - how societal movements can effectively re-embed neoliberal markets back into society - by drawing upon recent interpretations of Karl Marx writings on primitive accumulation and class formation. The author focuses on the case of Colombia's coffee farmers (cafeteros) - a class of producers whose historically-privileged modality of class reproduction was undermined by the liberalization of the coffee market in the 1990s and who have engaged in two major waves of protest aimed at re-embedding the coffee market back into society (1993-2001; 2013-2014). While similar in terms of movement targets, tactics, and general goals, a significant shift has occurred in the cafeteros' demands which is reflective of a fundamental transformation of their class identity away from one that 'naturalized' their dependence upon the coffee market to meet their subsistence needs and towards one that 'de-naturalizes' their dependence upon this market. This 'denaturalizatization of the market' undermined their ability to mobilize around a privileged form of class identity. Yet, it provided them with the ability to generalize their struggle beyond the confines of the coffee economy and therefore develop into a broad, national anti-neoliberal agrarian Polanyian counter-movement.
Sociology
Keywords: Colombia; Polanyi problem; countermovement; primitive accumulation; reembedding

Challenging Dominant Market Theories in Five Ways[1] - Janoski, Thomas (disClosure, 2015)
This article discusses why many social scientists including Karl Polanyi, Max Weber, and Karl Marx are dissatisfied with an overreliance on markets, and a conceptualization of markets being efficient, fair and rational. Topics include five types of arguments critical of markets including the Marxian approach to markets, the rise of Karl Polanyi's view that markets are fragile, and a more complex decision-making approach starting with Max Weber's view of social action.
Sociology
Keywords: MARX; Karl; 1818-1883; WEBER; Max; 1864-1920; markets; social action; social scientists